Analisis Bauran Pemasaran Dengan Strategi Segmenting, Targeting Dan Positioning Terhadap Penjualan Batik - Sarmini Sarmini; Ahmad Nihaul Khazani; Mohamad Irfan; Aris Maulana (Musamus University, Merauke Papua Indonesia., 2022)
To win market competition, companies must have segmentation, targeting, positioning and marketing. Of the four actions, it is necessary to include strategies related to the four activities, both individually and as a whole. This study aims to determine the segmentation, targeting, positioning strategy of Batik Products in Pekalongan. The data collected in this study are primary data and secondary data. Data collection methods in this study used interviews and documentation. The analytical technique used is descriptive analysis, which is a part of statistics that discusses how to collect data and collect observational figures obtained by collecting, summarizing, and presenting data. The results showed that the sales segmentation of Batik Products was the lower middle class. Considerations for choosing the lower social class because the company said that the number of lower middle class people was much larger than the upper middle class. The selected target market was the concentration segment or single market, product sales. Batik in the lower middle class of high quality.